Os efeitos da estimulação transcraniana por corrente contínua na dupla tarefa de indivíduos com doença de Parkinson: uma revisão sistemática - ARAÚJO, Ana Paula Monteiro de (Universidade Federal do Pará, 2023)
Introduction: In Parkinson's disease (PD), there are changes in brain connectivity, specifically in the motor areas and the cerebellum, when it is necessary to perform a Dual Task (DT). Added to the signs and symptoms, it causes negative repercussions on carrying out activities of daily living and the risk of falling, which is aggravated in TD conditions. On the other hand, Transcranial Direct Current Stimulation (tDCS) is capable of modulating the brain to establish new patterns of activity, acting on cognitive and motor variables, improving the functionality of these individuals. However, in the important context of TD, there is no review with this outcome in PD. Objective: To investigate whether isolated or associated tDCS is capable of altering the DT performance of people with PD. Methods: this review was based on the Core Items Guidelines for Reporting Systematic Reviews and Meta-Analyses (PRISMA) and was registered in the PROSPERO Database. The databases PubMed, Wiley, Scopus and Web of Science were used, without language or time restrictions. Clinical trials were included, which evaluated DT after tDCS (anodal or cathodal), isolated or associated when compared to the Sham or control group. Results: Only 4 studies were included. 62 participants were evaluated with Hoehn and Yahr (HY) minimum 1 and maximum 4.2 studies applied it alone (50%) and 2 studies associated it with physical exercise protocols (50%). Regarding the number of sessions, 3 authors evaluated a single session (75%) and 1 author evaluated 9 sessions (25%) associated with motor intervention. All used 2mA intensity. 3 authors used tDCS for 20 min (75%) and 1 author for 30 min (25%). 75% positioned the anode electrode in the Left Lateral Pre-Frontal Cortex (DLPFC) and the most used evaluation instrument was the Timed Up Go (75%). Conclusion: tDCS can have a positive effect on the performance of DT in PD, especially associated with pharmacological and non-pharmacological therapy. The main area stimulated was the left DLPFC, but the sample was not sufficient to define it as the best target. 20 minutes of stimulation seems to be sufficient and a greater number of sessions may provide a greater effect. Larger clinical trials with greater standardization are needed to allow better comparison between studies and reduce possible bias.